Let's solve the equation step by step, filling in the blanks.
-
Distribute to get:
\( 2(x - 3) + 21 = -3 \)
Distributing gives:
\( 2x - 6 + 21 = -3 \) -
Combine like terms to get:
Combining \(-6\) and \(21\) gives:
\( 2x + 15 = -3 \) -
Use the (choose a property):
We will use the Subtraction Property of Equality to isolate \(2x\):
Subtract \(15\) from both sides:
\( 2x + 15 - 15 = -3 - 15 \)
Resulting equation:
\( 2x = -18 \) -
Use the (choose a property):
Now we will use the Division Property of Equality to solve for \(x\):
Divide both sides by \(2\):
\( x = \frac{-18}{2} \)
Resulting answer:
\( x = -9 \)
So, the completed solution is:
- Distribute to get 2x - 6 + 21 = -3
- Combine like terms to get 2x + 15 = -3
- Use the (choose a property) Subtraction Property of Equality to get (resulting equation) 2x = -18
- Use the (choose a property) Division Property of Equality to get (resulting answer) x = -9.